As mediações no campo digital: uma pesquisa sobre a relação entre clube de futebol e torcedor na internet - Silva, Fernando Santos da (2018)
The current paper aims to analyze how the mediations and interactions occur on websites about soccer on the internet, whose specific objectives are: to analyze the official websites of Ceará Sporting Club, Ferroviário Atlético Clube and Fortaleza Atlético Clube, seeking to know the tools and the communicational and informational resources, and the possibilities of mediation; to investigate how the mediations and interactions are seen in the relationship between club and fan with the use of digital ways and analyze how the conversations on these virtual spaces are apprehended, both by the clubs and by the fans. It discourses upon the media and its characteristics, understanding it as a complex process composed by elements such as communication, culture, mediation, utilizing perspective of Cultural Studies to understand the relation between these categories. It emphasizes the main approaches of mediation in Information Science, pointing out how the conception of mediation from the symbolic bias helps to expand the ground’s view upon its research objects and its investigation fields, showing the soccer as a possible study field on this subject. It shows the soccer as a social and cultural phenomenon and its relation that exists between the sport and media. It exposes the characteristics of soccer’s dissemination through media, highlighting the proximity that exists between the two elements. It emphasizes the internet as one of the main media by which the sport popularizes and expands in contemporaneity. It is about a qualitative research of exploratory nature, which utilizes the ethnography and observation for field setting and data collection, besides network conversation for the analysis of the interactions between fans and clubs in social network. It concludes that the mediation on websites are from informational nature, since the organization of the information and the possibilities creation of senses and meanings according to what is published on the websites. It highlights the attitudes and motivations of the users and their own strategies of organization and appropriation of the information and the symbolic contents. It deduces that the interactions such as appropriations are settled in the actions of users to beyond what the tools can offer. The conversations are, therefore, examples of this appropriation, being undertaken mainly from social networks, which is used by both the clubs and fans. To understand that fans and clubs have become more autonomous to use the information and communication technologies, providing possibilities to Information Science with a broader understanding of production, organization and appropriation of information and mediation in virtual environments, considering cultural aspects in these processes. However, it highlights the possibility of expanding this approach from other perspectives on the same phenomenon.